2020
DOI: 10.1002/jcph.1676
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Recommendations for Pediatric Patients With Renal Impairment

Abstract: A treatment gap exists for pediatric patients with renal impairment. Alterations in renal clearance and metabolism of drugs render standard dosage regimens inappropriate and may lead to drug toxicity, but these studies are not routinely conducted during drug development. The objective of this study was to examine the clinical evidence behind current renal impairment dosage recommendations for pediatric patients in a standard pediatric dosing handbook. The sources of recommendations and comparisons included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…As shown in Table 3, all nine patients were treated for CMV with oral valganciclovir 14mg/kg twice daily. Doses may be renally adjusted, which occurred in one patient 9 . Of those nine, six (66.6%) received valganciclovir only for the treatment of CMV.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3, all nine patients were treated for CMV with oral valganciclovir 14mg/kg twice daily. Doses may be renally adjusted, which occurred in one patient 9 . Of those nine, six (66.6%) received valganciclovir only for the treatment of CMV.…”
Section: Resultsmentioning
confidence: 99%
“…One of the best examples of a need for dosing information in a specific pediatric patient population is the lack of current recommendations for pediatric dosing in renal impairment. A recent review of the evidentiary standards for those recommendations in a standard Wolters‐Kluwer Lexicomp pediatric dosing handbook demonstrated that <25% of those pediatric renal impairment dosing recommendations have any clinical information to substantiate the recommendation 56 …”
Section: Filling the Gap For Dosing In Pediatric Drug Developmentmentioning
confidence: 99%
“…The application of the same adult renal dosing recommendations to pediatric patients based on adult renal impairment PK data is most common 56 . This method assumes similar proportional effects of renal impairment on PK between adults and pediatric patients, but often without observed pediatric data to validate this assumption.…”
Section: Filling the Gap For Dosing In Pediatric Drug Developmentmentioning
confidence: 99%
“…Specific subpopulations are not addressed in pediatric anti-infective drugs development, such as children and neonates with kidney dysfunction or KRT. As pointed out in a recent review, clinical evidence in children does not exist for most renal dosing recommendations in a widely used pediatric dosing handbook, with the adult recommendations from the manufacturer's label being the primary source for pediatric dosing ( 4 ). Most studies on drug dosage in patients with kidney failure are performed in adults for ethical reasons, and off-label use is frequent in pediatrics.…”
Section: Introductionmentioning
confidence: 99%